Relationship Between Risk Factors and The Incidence of Gestational Trophoblastic Neoplasia at RSUP Dr. M. Djamil Padang Year 2019-2021 - Almujahid, Aldi; Syamel Muhammad; Asterina (Andalas Obstetrics And Gynecology Journal, 2024)
Background : Gestational Trophoblastic Neoplasia (GTN) is a tumor originating from cytotrophoblast and syncytotrophoblast that invades myometrium, damages surrounding tissue and blood vessels, and causing bleeding. Purpose : This study aims to determine the relationship between age, history of previous pregnancies, β-hCG levels, parity, and interval with last pregnancy on the incidence of GTN. Method : This research is an observational analytic study with a cross sectional research design. Univariate analysis was carried out which described the frequency distribution of variables and bivariate analysis with the chi square statistical test . Result : The results of this study showed that there was a significant relationship between age, history of previous pregnancies, β-hCG levels and parity) and the incidence of GTN, while the interval with the last pregnancy did not have a significant relationship with the incidence of GTN . Conclusion: It was concluded that age, history of previous pregnancy, β-hCG levels, and parity are risk factors for GTN.